Системний підхід до зниження екологічної небезпеки вентиляції резервуарів з нафтопродуктами - Гарбуз, Сергій Вікторович (НТУ "ХПІ", 2016)
Розглядається несприятливий екологічний вплив на довкілля викидів із резервуарів з залишками нафтопродуктів під час їх провітрювання перед проведенням ремонтних та інших видів робот. Наведені розрахунки щодо екологічного впливу об’єктів на атмосферу. Результатом досліджень є розроблений механізм системного підходу до зниження екологічної небезпеки вентиляції резервуарів з нафтопродуктами. Скорочення тривалості робіт з очищення резервуарів і зниження рівня пожежовибухонебезпеки при їх вентиляції потрібує вивчення всіх фізичних факторів та закономірностей, що впливають на цей процес.

The article examines cases of the adverse ecological impact on the environment of emissions from tanks of oil residues during their airing before the repairs or other types of preparatory works, as well as before the changing of the class of petroleum products. Reducing the duration of cleaning tanks and reducing the level of fire and explosion hazard during their ventilation requires exploring all physical factors and consistency that affect this process. At the article was shown a complex of mathematical calculations for various types of environmentally adverse impacts of objects on the atmosphere. The result of research is the developed mechanism of systematic approach to improve the environmental safety of the ventilation of tanks with petroleum products. Diesel oil, gasoline, toluene were used as fluids for research. Laboratory studies to water were used as a fluid for comparison. Supply air in the designed and constructed experimental tanks was supplied in four ways. Three of which have previously been studied and described in the literature (traditional supply, contrary and mixed), and also the supply which was developed by the author using the innovative ejector-vortex flow method. Its effectiveness is proven on several parameters – ventilation speed, environmental compatibility and efficiency.
A systematic approach to improve the environmental safety of the ventilation of tanks with petroleum products
Keywords: екологічна небезпека; атмосфера; забруднювачі повітря; вентиляція резервуарів; залишки нафтопродуктів; ecological safety; atmosphere; air pollutants; ventilation of tanks; oil residues